Little Dim Sum Warriors : translanguaging of Chinese and English in educational comic books for bilingual children - Istighfaroh, Anisatul; Yannuar, Nurenzia; Febrianti, Yusnita; Choiron, Nabhan Fuad; Basthomi, Yazid (Penerbit Universiti Kebangsaan Malaysia, 2022)
Comic books used to serve the purpose of entertainment; nowadays, they also provide one of the most innovative ways of learning. Not only do they stimulate brains with the visual mode, but they can also function as more effective teaching and learning resources with the usage of two modes: text and image. Referring to Kress’ (2010) framework on modes, this study investigates the translanguaging aspects of Little Dim Sum Warriors, a series of educational comic books with young bilingual or multilingual speakers as the target audience. This study focuses on how translanguaging, that is the fluid language practices of bilingual speakers (Wei, 2018), is present effectively in comic books by making use of Chinese culture (the learners’ home culture) when targeting English (learners’ target language) proficiency. In conducting the study, we analysed two storybooks of the series and collected the translanguaging practices found in both text and image formats. In our analysis we use Royce’s (1998) Intersemiotic Complementarity framework to assess the relation between verbal and visual modes. The results show that the translanguaging practices in comic books are divided into three forms: text, visual, and context-meaning. These practices help the audience understand foreign language and culture in a creative way, which fits the traits of young learners. Hence, keeping their attention in language learning intact.